(untitled) (Research, Society and Development, 2022)
In a descriptive and integrative approach, this work aims to verify the evolutionary process until the consolidation of Orofacial Harmonization as a specialty recommended by the Federal Council of Dentistry. Through the consultation of official documents, as well as the consultation of articles and scientific journals in the field of dentistry, we can analyze a justification that supports a new specialty through the applied theoretical frameworks. We try to raise understanding about the struggles between the Federal Council of Dentistry and the Federal Council of Medicine, associated with medical entities, through laws, rules and judicial procedures. Encourage an analysis of the legal aspects involved from 2011 to 2019, a year in which Orofacial Harmonization is considered a specialty in dentistry. The result of the resilience of the Federal Council of Dentistry in the face of the difficulties and the judicial struggles waged was the maintenance of such an important resolution for anatomical and scientific territories conquered using a capacity and as the contemporary, dynamic and evolutionary trends with observance of the Code of Dental Ethics.